Is the intensification of precipitation extremes with global warming better detected at hourly than daily resolutions?. Issue 2 (21st January 2017) - Barbero, R.; Fowler, H. J.; Lenderink, G.; Blenkinsop, S.
Abstract: Although it has been documented that daily precipitation extremes are increasing worldwide, faster increases may be expected for subdaily extremes. Here after a careful quality control procedure, we compared trends in hourly and daily precipitation extremes using a large network of stations across the United States (U.S.) within the 1950–2011 period. A greater number of significant increasing trends in annual and seasonal maximum precipitation were detected from daily extremes, with the primary exception of wintertime. Our results also show that the mean percentage change in annual maximum daily precipitation across the U.S. per global warming degree is 6.9% °C −1 (in agreement with the Clausius‐Clapeyron rate) while lower sensitivities were observed for hourly extremes, suggesting that changes in the magnitude of subdaily extremes in response to global warming emerge more slowly than those for daily extremes in the climate record. Key Points: We compared long‐term trends in hourly and daily precipitation extremes using quality‐controlled stations Upward trends in precipitation extreme were evident across the U.S., but overall, trends were better detected at daily resolutions than at hourly resolutions Daily precipitation extremes scale with mean global temperature following the CC rate, while hourly extremes show lower sensitivities